DEVELOPMENT OF RETROSPECTIVE LIFE-LONG PHYSICAL ACTIVITY QUESTIONNAIRE: FIRST STAGE - Ulmane, Zane; Šneidere, Kristīne; Stepens, Ainārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
With the increase in life expectancy and declining birth rates, the issue of improving the quality of life in people over 60 has become one of the priorities in health care (WHO, 2015). So far a limited number of studies have addressed the long-term relationship between aerobic exercise and cognitive processes (e.g. see systematic review by Young, Angevaren, Rusted, & Tabet, 2015). The aim of the study was to conduct the first stage in developing an instrument to retrospectively investigate life-time physical activity. Methods: a literature search in databases EBSCO, Pubmed, SCOPUS and Science Direct using keywords “retrospective physical activity”, “long-term physical activity” was conducted. After literature review, individual interviews with participants aged from 65 to 76 were held to create a retrospective physical activity questionnaire. Interviews were conducted according to literature-based protocol, which was updated after each participant. Results: eight main categories of life-time activity: "work”, “education", "sleep", "transportation", "self-care", "leisure time", "household activities" and "sports”. Conclusions: means of measuring life-long physical activity retrospectively would be highly beneficial in physical activity research; however, further work in developing and validating retrospective physical activity questionnaire is needed.